2020
DOI: 10.12659/msm.923618
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor κB/MicroRNA-155 Upregulates the Expression Pattern of Cytokines in Regulating the Relapse of Chronic Sinusitis with Nasal Polyps and the Underlying Mechanism of Glucocorticoid

Abstract: The aim of this study was to explore the upregulated nuclear factor kB (NF-kB)/microRNA-155 (miR-155) in regulating inflammatory responses and relapse of chronic rhinosinusitis (CRS) with nasal polyps (NP), which underlies the molecular mechanism of glucocorticoid treatment. Material/Methods: The study recruited 25 patients with eosinophilic (Eos) CRSwNP, 25 patients with Non-Eos CRSwNP, 25 patients with CRS without NP (CRSsNP) and 30 patients with nasal septum deviation (control group). The expression of NF-k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…For instance, upregulation of miR‐125b could increase IFN‐β expression in airway epithelial cells via targeting 4E‐BP1, thus hastening eosinophil infiltration 13 . Experimental evidence indicated that miR‐155 overexpression could result in the increase of tumor necrosis factor (TNF)‐alpha, IL‐1, IL‐4, and IL‐5 in the mouse model of eosinophilic CRSwNP 44 . It has been reported that the abnormal miR‐124 expression in CRSwNP could regulate cellular inflammatory response by inhibiting Aryl hydrocarbon receptor (AHR) expression 45 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, upregulation of miR‐125b could increase IFN‐β expression in airway epithelial cells via targeting 4E‐BP1, thus hastening eosinophil infiltration 13 . Experimental evidence indicated that miR‐155 overexpression could result in the increase of tumor necrosis factor (TNF)‐alpha, IL‐1, IL‐4, and IL‐5 in the mouse model of eosinophilic CRSwNP 44 . It has been reported that the abnormal miR‐124 expression in CRSwNP could regulate cellular inflammatory response by inhibiting Aryl hydrocarbon receptor (AHR) expression 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Activation of NF-κB signaling is associated with the production of various pro-inflammatory cytokines, including IL-1, IL-33 and thymic stromal lymphopoietin (TSLP), in human nasal epithelial cells ( 40 ). Glucocorticoid treatment, which is considered the first-line treatment of CRS ( 3 ), has been found to hinder the recurrence of CRS by inhibiting NF-κB signaling ( 41 ). Enhanced NF-κB pathway activation and increased IL-6 and IL-8 levels are observed in patients with CRS ( 42 ), implying the involvement of A20 in CRS pathogenesis and development.…”
Section: A20 In Allergic Airway Diseasesmentioning
confidence: 99%
“…The mechanism might be that miR-125b induces the production of type I interferon via targeting 4E-binding protein 1 (4E-BP1), an initiator of eukaryotic translation, in airway epithelial cells ( Zhang et al, 2012 ). Reports have shown that miR-155 is also upregulated in CRS ( Xia et al, 2015 ), particularly in ECRSwNP ( Du et al, 2020 ). The mechanism of miR-155 in ECRSwNP may involve the increase of inflammatory mediator cyclooxygenase 2 (COX2) and the decrease of anti-inflammatory mediator Src homology-2 domain-containing inositol 5-phosphatase 1 (SHIP1) ( Du et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Reports have shown that miR-155 is also upregulated in CRS ( Xia et al, 2015 ), particularly in ECRSwNP ( Du et al, 2020 ). The mechanism of miR-155 in ECRSwNP may involve the increase of inflammatory mediator cyclooxygenase 2 (COX2) and the decrease of anti-inflammatory mediator Src homology-2 domain-containing inositol 5-phosphatase 1 (SHIP1) ( Du et al, 2020 ). Furthermore, the mechanism of glucocorticoids in relieving recurrent CRSwNP is also closely related to the downregulation of miR-155 ( Du et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation